2019
DOI: 10.1002/ejp.1371
|View full text |Cite
|
Sign up to set email alerts
|

Strength and range of movement deficits are associated with symptom severity in people scheduled for hip arthroscopy

Abstract: Background Identifying the physical impairments associated with worse symptoms and greater functional limitations in people with hip pain could enable targeted rehabilitation programmes designed to improve quality of life. The objective of this study was to compare physical characteristics between subgroups of symptoms and functional limitation severity in individuals with hip pain scheduled for arthroscopic surgery. Methods Hip range of motion (ROM) and muscle strength were measured in 114 individuals (48 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…Also, an association between thickness of the hip capsule and lower ROM has been reported [ 33 ]. In one study, patients with FAIS with more severe symptoms had significantly lower flexion ROM [ 9 ]. In another study, elite football players who had a previous time-loss injury to the hip or groin were found to have significantly lower ROM, regardless of cam morphology [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, an association between thickness of the hip capsule and lower ROM has been reported [ 33 ]. In one study, patients with FAIS with more severe symptoms had significantly lower flexion ROM [ 9 ]. In another study, elite football players who had a previous time-loss injury to the hip or groin were found to have significantly lower ROM, regardless of cam morphology [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective cohort NR 14 200 NR 65 NR 24 Ellenrieder (2017) 21 Case series NR 12 c 30 44.2 38 45.4 3 Flores (2020) 22 Cohort 2 18 59 35.8 72 34.2 24 Frank (2016) 23 Prognostic cohort 2 21 75 37.38 75 38.41 24 Freke (2019) 24 Cross-sectional 3 16 66 NR 48 NR NR Fukushima (2021) 25 Retrospective cohort NR 11 c 5 46.2 0 NR 12 (mean: 40.2) Glein (2021) 28 Cohort 3 21 73 26.4 73 25.6 3, 12, annually Gupta (2016) 30 Case series 4 16 228 NR 367 NR 24 Haynes (2018) 33 Prospective cohort NR 15 254 NR 1321 NR 36 Hetsroni (2013) 34 Retrospective comparative, cross-sectional 45 Case series 4 12 c 810 NR 805 NR 18.7 (mean) Laurito (2021) 46 Retrospective cohort 2 16 131 39 63 43 17 (mean) Lee (2010) 47 Therapeutic case series (retrospective)…”
Section: Hos-ssmentioning
confidence: 99%
“…A limited ability to exert hip flexor force is likely due to a varying combination of pain inhibition [158], decreased neural drive and/or muscle weakness. The association between increased symptoms and decreased strength has been reported in previous studies that found individuals with hip pain who reported very low scores in the iHOT33 subscale of symptoms and functional limitations presented with significantly less flexion strength when compared to individuals with moderate or mild scores [62]. Hip strength deficits are consistently described in people with hip pain when compared to asymptomatic controls [64,67,119].…”
Section: Discussionmentioning
confidence: 71%
“…One hundred and forty-six patients aged 19-50 years (90 men) were recruited, seventy-eight were included in the final analysis (Figure 1). Data and methodology of collection from subsets of this cohort have been published in other papers [62,[64][65][66].…”
Section: Participantsmentioning
confidence: 99%